Faktor-Faktor Yang Mempengaruhi Minat Siswa Dalam Memilih SMKS 1 Jakarta - Anastasia Dwi Dharmaningrum; Siti Nurjanah (Research and Community Service UNIVERSITAS KALBIS, 2026)
This study aims to determine and analyze the factors that influence students' interest in the decision to choose a school at SMKS 1 Jakarta (case study at SMKS 1 Jakarta). This study is a quantitative study that aims to analyze the factors that influence interest in the decision to choose a school at SMKS 1 Jakarta. The population of the study was 204 respondents among SMKS 1 Jakarta students. The data collection method is quantitative, with technical analysis using confirmatory factor analysis (CFA). The results of the study showed that there were 11 factors formed from 7 variables that had been analyzed; these were the main factors formed in the analysis. In this case, schools can develop socialization activities, motivation regarding SMKS 1 Jakarta, majors, and information from the school environment, as well as support from the family environment, which will lead children to become enthusiastic and confident individuals to be able to have great motivation to learn, and a great deal of interest will also arise for students to be able to make decisions to choose at SMKS 1 Jakarta.